TRANSITIONING TO CLOUD TECHNOLOGIES: A COMPREHENSIVE GUIDE FOR IT PROFESSIONALS - Rohini Isarapu; Sharathchandra Gowda (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the transition pathway to cloud technologies for IT professionals, addressing the evolving landscape of cloud computing and its impact on career development. The article examines fundamental technical prerequisites, structured learning approaches, and strategic career transition methods. It details the importance of hands-on experience through practice environments, project implementation, and certification pathways while emphasizing the critical role of continuous learning and community engagement. The article covers essential aspects of cloud service models, platform-specific expertise, and the development of practical skills through real-world projects. The research-based approach provides insights into successful career transitions, skill assessment strategies, and portfolio development, offering a thorough framework for professionals seeking to establish themselves in cloud computing roles.